Understanding Motivation, Career Planning, and Socio-Cultural Adaptation Difficulties as Determinants of Higher Education Institution Choice Decision by International Students in the Post-pandemic Era - Zuo, Kun (Frontiers in Psychology, 2022)
The objective of this study is to understand motivation, career planning, and socio-cultural adaptation difficulties as determinants of higher education institution choice decisions by international students in the post-pandemic era. In reality, the modern drivers of globalism are facilitating the international students and the international students are facing different kinds of problems in the international institutes related to the cultural and socio-political issues. 260 questionnaires were considered to collect the data from the respondents of the study who were the international students getting an education in the high-class international institutes from China. The conclusion of this study demonstrates that international students are more concerned about cultural adoption, career planning, and personality development when they are willing to get admission to international institutes. Moreover, this study is designed to provide significant contribution to the theoretical and practical implications that address the gap in literature and practice. Also, this study provides significant future directions that are important to consider for future researchers to not repeat the same work but go with an alternative strategy.